Wortbildung mit exogenen Einheiten - Feine, Angelika (Glottodidactica, 2006)
Productive word formation of present-day German lexemes with exogenous elements, particularly confixes, has increased notably over the last few years. Consequentially these formations containing foreign elements have also attracted a great deal of attention among word formation researchers. Working towards an encyclopedic compilation of exogenous elements in German word formation it is demanded to crucially analyze these foreign elements in terms of etymological, structural, semantico-functional and textlinguistico-pragmatic criteria. This article provides insight into these aspects of analysis by examples of word-formation using exogenous elements such as -itis, -manie, -phob, and -aholic.